Численное решение обыкновенного дифференциального уравнения в случае дробной разности матричного оператора - Ilyin, I.A.; Noshchenko, D.S.; Perezhogin, A.S. (Vestnik KRAUNC: Fiziko-Matematičeskie Nauki, 2012)
Fractional power computation of matrix is represented. Numerical calculations for ordinary differential equation and its fraction analog is done. Results are compared with Grunvald – Letnikov operator.